2006
DOI: 10.1016/j.jcrs.2006.02.070
|View full text |Cite
|
Sign up to set email alerts
|

Corneal endothelial damage after cataract surgery: Microincision versus standard technique

Abstract: No significant differences in corneal endothelial cell loss or endothelial morphology were found between MICS and standard incision techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
101
3
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(117 citation statements)
references
References 20 publications
8
101
3
5
Order By: Relevance
“…Operative parameters such as surgery time, phaco time, mean ultrasound power, and corneal tunnel length, as well as irrigation solution turbulence, instrument-related trauma, intraocular lens (IOL) contact, nuclear fragments, type of the implanted intraocular lens, and type of viscoelastic substances were associated with endothelial cell loss [11,7,[12][13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…Operative parameters such as surgery time, phaco time, mean ultrasound power, and corneal tunnel length, as well as irrigation solution turbulence, instrument-related trauma, intraocular lens (IOL) contact, nuclear fragments, type of the implanted intraocular lens, and type of viscoelastic substances were associated with endothelial cell loss [11,7,[12][13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies found that the degree of induced astigmatism after bimanual MICS is equal to or even less than that of conventional coaxial small incision cataract surgery [4,7,19,23] and that the tissue damage from bimanual MICS is comparable to that from small incision cataract surgery [19,[23][24][25][26][27] . However, there are some disadvantages to B-MICS including wound damage, difficulties in mastering the technique, leakage due to thermal burn and the need for wound enlargement for IOL implantation [2,5,10,28,29] .…”
Section: Discussionmentioning
confidence: 99%
“…16,17,[20][21][22] However, the incision site, operative technique, and measurement methods vary and lead to different results. Recently, in a large series of 433 patients, Bourne et al 16 found a mean reduction in endothelial cell count of 16.1 and 14.2% 12 months following phacoemulsification and extracapsular cataract extraction, respectively.…”
Section: Discussionmentioning
confidence: 99%